QUANTITATIVE APPROACH TO SUSTAINABILITY ASSESSMENT OF THE USE OF COASTAL ECOSYSTEMS - Lan, Tran Dinh (Vietnam Journal of Marine Science and Technology, 2014)
Sustainable use of coastal ecosystems in the case studies of some partner countries of SECOA project, including Belgium, India, Israel, Portugal and Vietnam was assessed through sustainability indicator analysis and index calculation. The outcomes were shown quantitatively with values of sustainability indices of the coastal ecosystem at time points within assessed periods. Based on these outcomes, three tendencies were evident, including: the declination from sustainable use to unsustainable use, event to very unsustainable use shown in the case studies of India, Israel and Vietnam, the maintenance of sustainable use presented in the case studies of Portugal, and the unclear tendency occurred in the case studies of Belgium.